Automatic extrinsic calibration of multiple laser range sensors with little overlap - Rowekamper, Jorg; Ruhnke, Michael; Steder, Bastian; Burgard, Wolfram; Tipaldi, Gian Diego (Proceedings - IEEE International Conference on Robotics and Automation, 2015)
Networks of laser range finders are a popular tool for monitoring large cluttered areas and to track people. Whenever multiple scanners are used for this purpose, one major problem is how to determine the relative positions of all the scanners. In this paper, we present a novel approach to calibrate a network of multiple planar laser range finders scanning horizontally. To robustly deal with the potentially restricted overlap between the fields of view, our approach only requires a dynamic object, e.g., a person, moving through the observed area. We employ a RANSAC-like algorithm to find the correspondences between the measurements of the different laser range finders. Based on these correspondences we formulate a graph-based optimization problem to determine the maximum likelihood extrinsic parameters of the sensor network. Furthermore, we present a method to evaluate the consistency of the resulting calibration based on visibility constraints. Experiments on real and simulated data show that the proposed approach yields better results than techniques that only perform pairwise calibration.